Efficiency testing of local bacterial isolates in controlling wheat common bunt, Tilletia tritici (Damascus University Journal of agriculture sciences, 2025)
The aim of this study was to evaluate the effect of wheat seed treatment using local bacterial isolates in controlling common bunt disease, caused by the fungus Tilletia tritici, through a field experiment carried out in 2022. 150 bacterial strains were isolated from 16 soil samples (from cultivated fields with wheat or other crops and uncultivated fields), in Damascus, Lattakia and Hama governorates. The effect of these bacterial isolates was tested for inhibition of teliospores germination of Tilletia tritici on water agar in vitro, and 14 bacterial isolates showed significant effect in inhibiting the spore germination and were used in the field experiment. Wheat seeds previously inoculated with common bunt teliospores were treated with the selected bacterial isolates. Results showed that the bacterial isolate B3 demonstrated the highest efficiency in inhibiting the disease with an infection rate of 34.86% compared to the untreated inoculated control with a high infection rate of 85.2%, while the infection rate of the chemical pesticide treatment (Carboxin + Thiram) was 58.9%. Five other isolates showed relatively high efficiency as well (infection rate from 35.5% to 40.3%). The results showed the possibility of using antagonist bacteria in the control of common bunt as an organic alternative to chemical fungicides. This could necessitate efficiency testing of mixtures containing more than one bacterial isolate to obtain high efficiency.
Keywords: Wheat Common Bunt; Tilletia Tritici; Antagonist Bacterial Isolates